2020
DOI: 10.1155/2020/5293850
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Proangiogenic Effects of Adipose-Derived Stem Cells and Foreskin Fibroblast Exosomes on Artificial Dermis Prefabricated Flaps

Abstract: Large prefabricated flaps often suffer from necrosis or poor healing due to a lack of new blood vessels and related factors that promote angiogenesis. The innovative use of adipose-derived stem cell exosomes (ADSC-Exo) resolves the problem of vascularization of prefabricated flaps. We analyzed the differential microRNA (miRNA) expression in ADSC-Exo using nextgeneration sequencing (NGS) technology to explore their potential mechanisms in promoting vascularization. We observed that ADSC-Exo could significantly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 45 publications
1
19
0
Order By: Relevance
“…Two studies found that ASCs EVs could inhibit the proliferation/migration, and promote the apoptosis of keloid/hypertrophic scar fibroblasts via the regulation of miR-192-5p/IL-17RA/Smad axis [ 23 ] or inhibiting TGF-β1/Smad pathway [ 174 ]. Another two studies reported the essential roles of ASCs EVs in promoting the vascularization of skin flaps [ 163 , 176 ], and one study found that ASCs EVs were comparable to parent ASCs in the inhibition of alloimmune response for vascularized composite allotransplantation [ 13 ]. Recently, ASCs EVs have been investigated in the antiaging of photoaged skin by increasing the mRNA expression of type I collagen, corresponding to the antiaging properties of parent ASCs [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…Two studies found that ASCs EVs could inhibit the proliferation/migration, and promote the apoptosis of keloid/hypertrophic scar fibroblasts via the regulation of miR-192-5p/IL-17RA/Smad axis [ 23 ] or inhibiting TGF-β1/Smad pathway [ 174 ]. Another two studies reported the essential roles of ASCs EVs in promoting the vascularization of skin flaps [ 163 , 176 ], and one study found that ASCs EVs were comparable to parent ASCs in the inhibition of alloimmune response for vascularized composite allotransplantation [ 13 ]. Recently, ASCs EVs have been investigated in the antiaging of photoaged skin by increasing the mRNA expression of type I collagen, corresponding to the antiaging properties of parent ASCs [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, Western blot analyses of each protein or phosphorylated protein with investigation of the function of these proteins on endothelial cells is necessary to confirm the conclusions. Moreover, the effect on angiogenesis by exosomes secreted from ADSCs upon LPS stimulation may rely on factors other than the protein cargo inside exosomes, such as microRNAs [80,81] or lncRNAs [82], which are known to mediate the function of ADSCs on angiogenesis, and should be considered accordingly. Furthermore, LPS, the stimulator used in this study, is only one of a common bacterial toxin component in infectious wounds.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, growth factor therapy is not currently considered an effective treatment based on preclinical and clinical studies [ 39 ]. Exosomes types of membranous vesicles with a diameter of approximately 30–100 nm that are released from cells into the ECM [ 40 ]. Stem cell exosomes can carry a variety of growth factors and noncoding RNAs, which serve as a medium for cell-to-cell communication and target the biological functions of cells [ 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%